Characterizing food safety aspects of the Cambodian vegetable value-chain: a quantitative and qualitative investigation of biological hazards and food safety practices in Cambodia - Desiree, Karina (Kansas State University, 2019)
Food safety is a major challenge in low and middle-income countries (LMIC). In Cambodia, diarrheal disease is a prominent cause of childhood mortality. Recent findings suggest that greater than 40% of diarrheal diseases in developing nations are attributed to contaminated food. The majority of consumers in Cambodia purchase food through informal markets that escape food safety standards and controls. This is primarily due to the fact that food safety regulations are often poorly enforced, and infrastructural and educational capacity for food safety is limited, particularly in informal market settings. This is critical, since a majority of consumers in LMIC purchase vegetables that are often consumed raw through informal markets. The consumption of contaminated raw vegetables is heavily linked to foodborne illness, and likely contributes to morbidity and mortality in the country. Currently, little data exists on the biological contamination (i.e. bacteria, viruses, and parasites) of vegetables being sold in informal markets in Cambodia. This research seeks to investigate “What is the prevalence and concentration of bacterial hazards on vegetables sold in Cambodian informal markets, and how do handling practices, from farm- to-market, contribute to food safety outcomes in the vegetable value-chain of Cambodia?”. Based upon this, the following objectives were chosen: (1) to investigate the prevalence and concentration of Salmonella enterica, as well as the concentration of generic Escherichia coli (E. coli) and coliforms, on different types of fresh vegetables sold in Cambodian informal markets in different seasons; (2) to define the flow and the behaviors of stakeholders within the Cambodian vegetable value-chain through personal interviews; and (3) to identify practices that can potentially contribute to the cross-contamination of vegetables moving through the value-chain. It was hypothesized that the prevalence and concentration of bacterial hazards would vary by vegetable type and seasons, due to differences in food matrix and growth conditions, as supported by scientific literature. Furthermore, it was hypothesized that due to limited educational, physical and regulatory capacity, the likelihood of poor handling practices by vegetable value-chain actors would be high, and contribute to contamination of vegetables along the value chain. Three types of vegetables (lettuce, tomatoes, cucumbers) were collected from informal markets located in two different provinces (Battambang and Siem Reap) in Cambodia in two different seasons (rainy and dry). Samples were subjected to validated methods for the detection of Salmonella enterica, and the enumeration of Salmonella enterica, generic E. coli, and coliforms. Presumptive positive isolates of Salmonella enterica were confirmed using Real-Time PCR. Further, a survey tool was used to investigate the flow of the Cambodian vegetable value-chain, and personal interviews with value-chain actors was used to characterize food safety practices within this value-chain (i.e. farmer, collector, distributor and vendor). The highest prevalence of Salmonella enterica was found on lettuce collected in the dry season (55.8%), whereas the lowest prevalence was found on lettuce collected in the rainy season (15.4%). In terms of concentration of Salmonella enterica, lettuce had a significantly higher concentration (5.66 log10 CFU/g), as compared to cucumbers (4.20 log₁₀ CFU/g) and tomatoes (3.99 log CFU/g). Further, vegetables in the rainy season (5.27 log₁₀ CFU/g) had significantly higher counts of Salmonella enterica as compared to vegetables in the dry season (3.96 log CFU/g). Moreover, the highest concentration of E. coli and coliforms were observed on lettuce during the rainy season (2.75 and 6.31 log₁₀ CFU/g respectively). Conversely, the lowest concentration of E. coli and coliforms were observed on cucumbers (0.81 log₁₀ CFU/g) and tomatoes (3.89 log₁₀ CFU/g) collected in the dry season. Survey results support that a high percentage of the value-chain actors do not practice cool storage, which increases the likelihood of microbial proliferation as well as decrease the quality of vegetables. Additionally, the wide use of inadequately composted animal-source waste, contaminated irrigation water, and the lack of basic food hygiene practices (e.g. using fabric gloves, selling raw meat in the same area as fresh vegetables, lack of handwashing practices etc.) were factors that may be contributing to the introduction of pathogens through cross-contamination. Findings from this study highlighted that vegetables sold in informal markets in Cambodia are contaminated with biological hazards, with high concentrations being observed across all vegetable types and seasons. Contaminated vegetables can introduce bacterial pathogens into informal markets. Furthermore, contamination may be increased through the lack of basic food hygiene practices of value-chain actors, particularly informal market vendors. Many of these practices promote cross-contamination of bacteria from the environment to the vegetables. For these reasons, interventions such as food safety recommendations in the form of training and education programs for value-chain actors, regulatory coordination, consumer communication programs and infrastructure development are necessary to reduce the likelihood of contamination and negative public health outcomes in the country.
Keywords: Food safety; Cambodia; Informal market; Vegetables; Salmonella; Escherichia coli